Endocrine disruptors and puberty - Gore, Andrea C.; Diamanti-Kandarakis, Evanthia (Contemporary Endocrinology, 2012)
Endocrine disruption represents one of the most controversial environmental issues of our time. Mounting evidence stemming from more than 10 years of experimental, epidemiological and clinical studies has transformed the once generally discounted subject of endocrine disruptors into an issue of tremendous concern not only within the scientific community but among society as a whole.  Following initial evidence from basic research, endocrine disruption in humans has now emerged as a major medical challenge.  In this respect, puberty, a crucial developmental stage, has been definitively identified as a key window of vulnerability with regard to endocrine disruptors.  Written by leading authorities in the field, Endocrine Disruptors and Puberty offers an engaging and comprehensive overview of this fascinating and rapidly growing problem.  An indispensable resource for all clinicians and scientists interested in this challenging endocrinologic topic, Endocrine Disruptors and Puberty is a timely contribution that will help navigate a path toward understanding the problem and developing solutions.